A SOCIOPRAGMATIC ANALYSIS OF SYMPATHY AND EMPATHY EXPRESSIONS ON INSTAGRAM: INSIGHTS FROM A VIDEO OF CHILDREN IN GAZA - Puspitasari, Mawar; Siti Zuhriah Ariatmi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
The genocide committed by Israel in Gaza is still ongoing to this day. This action has received enormous attention from people from all over the world because it has claimed many victims ranging from children, adults, to the elderly. The purpose of this study is to describe the types of expressions of sympathy and empathy and to clarify the intention of sympathy and empathy expressions  given by Instagram users to videos of children in Gaza. This study used a qualitative descriptive method. This study used observation and documentation methods to find the data. Research reveals that there are 2 types of sympathy, namely passive sympathy and active sympathy. This study also reveals that there are 3 types of empathy, namely cognitive empathy, emotional empathy, and compassionate empathy. As for the type of intention, 13 speech acts were found in this study, namely requesting, begging, proposing, vowing, thanking, apologizing, regretting, lamenting, blaming, praising, wishing, condoling, and criticizing. The findings of this study can be used to broaden understanding and make it easier for readers to distinguish expressions of sympathy and empathy.